Power Of Love In Pride And Prejudice By Jane Austen (1813):A Psychoanalytic Approach - Setiyawati, Vima; , Drs. Abdillah Nugroho, M.Hum; , Drs. Sigit Haryanto, M. Hum (2013)
1813). This objective of the study is to analyze the structural element on the novel and to describe the power of love in Pride and Prejudice novel. This study belongs to qualitative study. In this method, the writer uses two types of the data source, namely primary and secondary data source. The primary data source and the object of the study is the novel itself, meanwhile the secondary is any literature related to this study for example reading some other resources related to the novel, website, book, and etc. The writer collects the data from both primary and secondary data source in sort of document as evidence. The technique of analyzing data is descriptive. Having analyzed this novel, the writer draws some conclusions as follows. First, based on the structural analysis, the writer successfully delivers the moral message through the excellent unity of structural element. The writer wants to say that love can come pride and prejudice of someone, but with the conviction of heart that all of prejudice will be destroyed, but with the conviction that the hearts of all prejudices will disappear Second, based on the A Psychoanalytic Approach, Jane Austen's describe the differences in character and characterization are not important in a relationship. They can even bring a good luck to them.